The prevalence and determinants of anti-DFS70 autoantibodies in an international inception cohort of systemic lupus erythematosus patients. (September 2017) - Choi, M Y; Clarke, A E; St Pierre, Y; Hanly, J G; Urowitz, M B; Romero-Diaz, J; Gordon, C; Bae, S-C; Bernatsky, S; Wallace, D J; Merrill, J T; Isenberg, D A; et al.
Autoantibodies to dense fine speckles 70 (DFS70) are purported to rule out the diagnosis of SLE when they occur in the absence of other SLE-related autoantibodies. This study is the first to report the prevalence of anti-DFS70 in an early, multinational inception SLE cohort and examine demographic, clinical, and autoantibody associations. Patients were enrolled in the Systemic Lupus International Collaborating Clinics (SLICC) inception cohort within 15 months of diagnosis. The association between anti-DFS70 and multiple parameters in 1137 patients was assessed using univariate and multivariate logistic regression. The frequency of anti-DFS70 was 7.1% (95% CI: 5.7–8.8%), while only 1.1% (95% CI: 0.6–1.9%) were monospecific for anti-DFS70. In multivariate analysis, patients with musculoskeletal activity (Odds Ratio (OR) 1.24 [95% CI: 1.10, 1.41]) or with anti-β2 glycoprotein 1 (OR 2.17 [95% CI: 1.22, 3.87]) were more likely and patients with anti-dsDNA (OR 0.53 [95% CI: 0.31, 0.92]) or anti-SSB/La (OR 0.25 [95% CI: 0.08, 0.81]) were less likely to have anti-DFS70. In this study, the prevalence of anti-DFS70 was higher than the range previously published for adult SLE (7.1 versus 0–2.8%) and was associated with musculoskeletal activity and anti-β2 glycoprotein 1 autoantibodies. However, 'monospecific' anti-DFS70 autoantibodies were rare (1.1%) and therefore may be helpful to discriminate between ANA-positive healthy individuals and SLE.